2005
DOI: 10.1016/j.cogbrainres.2005.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological correlates of facial decision: Insights from upright and upside-down Mooney-face perception

Abstract: We investigated the ERP correlates of the subjective perception of upright and upside-down ambiguous pictures as faces using two-tone Mooney stimuli in an explicit facial decision task (deciding whether a face is perceived or not in the display). The difficulty in perceiving upside-down Mooneys as faces was reflected by both lower rates of "face" responses and delayed "face" reaction times for upside-down relative to upright stimuli. The N170 was larger for the stimuli reported as "faces". It was also larger f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
78
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(92 citation statements)
references
References 52 publications
12
78
2
Order By: Relevance
“…N170 amplitude is also larger in response to Mooney faces (high-contrast two-tone pictures of faces only depicting shadow versus light information, see Fig. 3) that are consciously perceived as faces versus Mooney faces that are not perceived as faces, suggesting that the identification of a stimulus as a face is related to the N170 response [72] , though there is also evidence that the N170 can be elicited in response to unconsciously perceived faces in patients with neglect [73] .…”
Section: The Neurophysiology Of Face Processingmentioning
confidence: 90%
“…N170 amplitude is also larger in response to Mooney faces (high-contrast two-tone pictures of faces only depicting shadow versus light information, see Fig. 3) that are consciously perceived as faces versus Mooney faces that are not perceived as faces, suggesting that the identification of a stimulus as a face is related to the N170 response [72] , though there is also evidence that the N170 can be elicited in response to unconsciously perceived faces in patients with neglect [73] .…”
Section: The Neurophysiology Of Face Processingmentioning
confidence: 90%
“…The N170 component of the event-related potential, which occurs specifically in response to the image of a face (Bentin, Allison, Puce, Perez, & McCarthy, 1996), is also observed in response to the presentation of Mooney faces; and when the Mooney face is consciously perceived, the amplitude of this component is increased (George, Jemel, Fiori, Chaby, & Renault, 2005;Jeffreys, 1989;Jemel, Pisani, Calabria, Crommelinck, & Bruyer, 2003;Latinus & Taylor, 2005). Furthermore, the highly face-selective fusiform face area shows increased activity upon the conscious perception of a Mooney face, as compared to the failure to perceive it (Andrews & Schluppeck, 2004;Kanwisher et al, 1998;Rossion, Dricot, Goebel, & Busigny, 2011).…”
mentioning
confidence: 84%
“…A host of studies have shown the strong sensitivity of N170 to human faces, as reflected by larger amplitude to faces than a variety of objects (Bentin et al, 1996;Eimer, 2000;Itier et al, 2006;Rossion et al, 1999), whether the stimulus is a schematic, sketch, painting, drawing or photograph of a human face (Sagiv and Bentin, 2001), or a twotone Mooney figure perceived as a face (George et al, 2005;Latinus and Taylor, 2005). The N170 is generally viewed as a marker of the encoding stage of the face structure (Eimer, 2000;Rossion et al, 1999), when the perceptual representation of a face is being created, although its sensitivity to identity is still actively debated (e.g.…”
Section: Introductionmentioning
confidence: 99%